Molecular identification and characterization of Pseudomonas stutzeri strain showing potent degradation activity towards pyrene - Mohammad Ali, Hani (Journal of King Abdulaziz University: Science, 2024)
Pyrene is a Polyaromatic hydrocarbon ubiquitously found in soils. Bioremediation of this lethal and toxic compound is of utmost importance due to its toxicity toward humans. It is imperative to identify and isolate bacterial species that readily degrade pyrene present in the soil. In this study soil samples were collected from different regions in the Madinah region and studied for the presence of bacterial species that readily degrade pyrene. Isolates were thoroughly studied for the degradation of Pyrene using Spectrophotometer, DCPIP Assay, and dry weight method. About 18 bacterial isolates were isolated from soil samples of Madinah. Among them, only P12 show high degradation activity. Furthermore, the potent strains were Identified using 16s rRNA gene sequencing as Pseudomonas stutzeri. Results show that Pseudomonas stutzeri change color from blue to white in the presence of DCPIP dye compare to the control one. The optical density of this strain was also high at 600 nm wavelength compare to the other strains. High Pressure Liquid Chromatography analysis shows that one of the selected sample P12 shows 100 % degradative activity compare to the control one. The dry weight also confirms its degradative activity towards pyrene. Our study concludes that these strains can be used to clean the environment.